Reliability of Bolton analysis evaluation in tridimensional virtual models - Marianna Mendonca Brandão; Marcio Costal Sobral; Carlos Jorge Vogel (Dental Press Editora, 2015)
Objective: The present study aimed at evaluating the reliability of Bolton analysis in tridimensional virtual models, comparing it with the manual method carried out with dental casts.Methods:The present investigation was performed using 56 pairs of dental casts produced from the dental arches of patients in perfect conditions and randomly selected from Universidade Federal da Bahia, School of Dentistry, Orthodontics Postgraduate Program. Manual measurements were obtained with the aid of a digital Cen-Tech 4"(r) caliper (Harpor Freight Tools, Calabasas, CA, USA). Subsequently, samples were digitized on 3Shape(r)R-700T scanner (Copenhagen, Denmark) and digital measures were obtained by Ortho Analyzer software.Results:Data were subject to statistical analysis and results revealed that there were no statistically significant differences between measurements with p-values equal to p = 0.173 and p= 0.239 for total and anterior proportions, respectively.Conclusion:Based on these findings, it is possible to deduce that Bolton analysis performed on tridimensional virtual models is as reliable as measurements obtained from dental casts with satisfactory agreement.